Synthesis and dielectric properties of strontium substituted calcium niobate ceramics - Yim, Haena; Yoo, So Yeon; Sung, Yung-Eun; Choi, Ji-Won (ELSEVIER SCIENCE SA, 2015)
Layered perovskite KCa2(1-x)Sr2xNb3O10 ceramic (x = 0, 0.2, 0.4, 0.6, 0.8 and 1) materials were prepared by a conventional solid-state reaction method, and the effects of Sr substitution for Ca on the crystal structure and dielectric properties of the KCa2(1-x)Sr2xNb3O10 system were investigated. Also, potassium ions were exchanged with proton ions to obtain HCa2(1-x)Sr2xNb3O10. Then, X-ray diffraction, infra-red spectra, and energy dispersive detector analysis were carried out to verify immaculate substitution. Unlike alkali cations intercalated powder, the dielectric properties of 2Ca((1-x))Sr(x)Nb(2)O(6)-Ca2(1-x)Sr2xNb2O7 mixtures, which were obtained from HCa2(1-x)Sr2xNb3O10 by sintering, showed high dielectric permittivity with increasing amounts of strontium, and remained unaffected by frequency change from 1 kHz to 1 MHz. Its compositional dependence behavior was analyzed through Raman spectral analysis. X-ray diffraction, differential thermal analysis, and thermogravimetry observation revealed the phase transition on sintering of HCa2(1-x)Sr2xNb3O10. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: LAYERED PEROVSKITE; KCA2NB3O10; NANOSHEETS